2018
DOI: 10.1186/s12918-018-0642-2
|View full text |Cite
|
Sign up to set email alerts
|

GSAE: an autoencoder with embedded gene-set nodes for genomics functional characterization

Abstract: BackgroundBioinformatics tools have been developed to interpret gene expression data at the gene set level, and these gene set based analyses improve the biologists’ capability to discover functional relevance of their experiment design. While elucidating gene set individually, inter-gene sets association is rarely taken into consideration. Deep learning, an emerging machine learning technique in computational biology, can be used to generate an unbiased combination of gene set, and to determine the biological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…We will continue our work to investigate this issue by introducing yet another rich source of transcriptomic data from GTEx collection [33]. Furthermore, as suggested by previous studies [13,15,[34][35][36][37], we may incorporate additional genome-wide profiling information, such as DNA mutation, copy number variation, and DNA methylation as additional input matrices to enrich the complexity for model training, and thus to improve the classification accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will continue our work to investigate this issue by introducing yet another rich source of transcriptomic data from GTEx collection [33]. Furthermore, as suggested by previous studies [13,15,[34][35][36][37], we may incorporate additional genome-wide profiling information, such as DNA mutation, copy number variation, and DNA methylation as additional input matrices to enrich the complexity for model training, and thus to improve the classification accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our earlier attempts [15], Chen, et al, constructed an autoencoder system (GSAE) with embedded pathways and functional gene-sets at each input node to reduce -6 -the number of weights to be estimated. They applied the GSAE to classify breast cancer subtypes.…”
mentioning
confidence: 99%
“…For that purpose, Tan et al used denoising AEs derived from the transcriptomics of Pseudomonas aeruginosa and found a representation where each node coincided with known biological pathways (Tan et al 2016). Chen et al used cancer data and showed that starting from pathways represented as a priori defined hidden nodes, allowed the investigators to explain 88% of variance, which in turn produced an interpretable representation (Chen, et al, 2018). These results demonstrate that AEs can use pre-defined functional representations, and can learn such representations from input data, although systematic evaluation of how to balance between pre-defined features versus purely data-driven learning remains to be determined.…”
Section: Dnn Architectures Are Hierarchically Organized Layers Of Nonmentioning
confidence: 99%
“…Gene superset, which is an unbiased combination of gene sets, is the topic of the next paper. In the next study by Chen et al [4], the authors proposed a gene superset autoencoder (GSAE), a multi-layer autoencoder model with the incorporation of a priori defined gene sets that retain the crucial biological features in the latent layer. They introduced the concept of the gene superset, an unbiased combination of gene sets with weights trained by the autoencoder, where each node in the latent layer is a superset.…”
Section: The Science Program For the Icibm 2018 Systems Biology Trackmentioning
confidence: 99%